Analysis Strengthening Business Strategy and Human Resource Capacity for Sustainable Small and Medium Enterprise Development - N. Nurlaela; Eka Merdekawati; S. Sarnawiah (Manunggal Halim Jaya, 2026)
Small and Medium Enterprises (SMEs) play a vital role in promoting economic growth, employment generation, and community welfare; however, many SMEs continue to encounter challenges related to strategic management and human resource capability that hinder their long-term sustainability. This community engagement program aimed to strengthen business strategy and enhance human resource capacity to improve the competitiveness and sustainable development of SMEs. The program adopted a participatory capacity-building approach involving needs assessment, business strategy workshops, human resource development training, mentoring, coaching, and program evaluation. Interactive learning methods, including discussions, case studies, business simulations, and individualized mentoring, were employed to facilitate knowledge transfer and practical implementation. Program evaluation was conducted using pre-test and post-test assessments, observations, interviews, focus group discussions, mentoring records, and participant satisfaction questionnaires. The findings indicate that participants demonstrated improved understanding of strategic business planning, organizational management, leadership, customer service, and sustainable business practices. The mentoring process further enabled SME owners to formulate strategic business plans, improve managerial decision-making, strengthen workforce competencies, and increase organizational readiness for business development. Participants also expressed high satisfaction with the relevance and applicability of the training activities. These findings suggest that integrating business strategy development with human resource capacity building provides a comprehensive and sustainable approach to enhancing SME competitiveness. This program highlights the strategic role of higher education institutions in empowering local enterprises through knowledge transfer and collaborative capacity-building initiatives that contribute to sustainable economic development.